Agricultural Landscapes in urban environments by the example of Christchurch, New Zealand - Attila Tóth; Ľubica Feriancová (Acta Scientiarum Polonorum. Formatio Circumiectus)
Agriculture has diverse forms in the intra-urban and peri-urban area of Christchurch, the capitol of the Canterbury Region, New Zealand. These agricultural landscapes are productive components of the urban green infrastructure and provide important environmental, social and economic services. Within the Reciprocal Short Term Scientific Mission supported by the European Cooperation in Science and Technology, diverse patterns of urban agriculture have been analysed according to their spatial and structural characteristics and considering their significance for building a resilient urban food system. The aim of this paper is to introduce and analyse different patterns of urban agriculture by four case studies in the intra-urban area and two case studies in the peri-urban area of Christchurch. The intra-urban agricultural landscapes are represented by the Okeover Community Garden at the University of Canterbury, the Christchurch Farmers Market at the Riccarton House, The Agropolis Urban Farm and an urban production garden. The agriculture in the peri-urban area of the city is introduced as large-scale agriculture and a specific form of urban sprawl and arable land consumption is presented by the example of lifestyle blocks.